Nephrotoxicity of CCA-treated wood: a comparative study with As2O5 and CrO3 on mice - Matos, Rita Cerejeira (2013)
The purpose of this work was to assess the acute toxicity on male mice to a chromated copper arsenate (CCA) solution, a widespread wood preservative used in building industry until 2002. Animals were subcutaneously injected with CCA (7.2 mg/kg arsenic and 10.2 mg/kg chromium per body weight), CrO3 (10.2 mg/kg), As2O5 (7.2 mg/kg) and NaCl (0.9%) per se, during 48 h and 96 h, for histopathology, histochemistry, chromium and arsenic analysis. The results showed some histopathological changes within renal tubules lumen of CCA exposed animals (during 48 h, and 96 h), and CrO3 (for the period of 96 h). Furthermore, the renal levels of arsenic and chromium in treated animals were statistically more evident than controls. Although, the same contents of pentavalent arsenic and hexavalent chromium were injected into treated animals with CCA and with the prepared solutions of As2O5 and CrO3, a different distribution of the pattern of these compounds was observed in kidneys.